2018
DOI: 10.1186/s12884-018-1661-0
|View full text |Cite
|
Sign up to set email alerts
|

Women’s decision-making processes and the influences on their mode of birth following a previous caesarean section in Taiwan: a qualitative study

Abstract: BackgroundVaginal birth after caesarean (VBAC) is an alternative option for women who have had a previous caesarean section (CS); however, uptake is limited because of concern about the risks of uterine rupture. The aim of this study was to explore women’s decision-making processes and the influences on their mode of birth following a previous CS.MethodsA qualitative approach was used. The research comprised three stages. Stage I consisted of naturalistic observation at 33-34 weeks’ gestation. Stage II involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
74
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 44 publications
10
74
0
Order By: Relevance
“…The current caesarean section for 33 (20.2%) of the respondents was due to previous CS, giving a high incidence (60%) among this category of respondents. This is consistent with ndings of earlier researches on the possibilities of having repeat CS [27] and the respondents' fore-knowledge of this in uenced their decision-making [28,29]. This was however contrary to ndings where respondents with previous CS were reluctant to have another CS because of fear of death and mockery [20] which contributed to women preferring vaginal delivery.…”
Section: Discussionsupporting
confidence: 88%
“…The current caesarean section for 33 (20.2%) of the respondents was due to previous CS, giving a high incidence (60%) among this category of respondents. This is consistent with ndings of earlier researches on the possibilities of having repeat CS [27] and the respondents' fore-knowledge of this in uenced their decision-making [28,29]. This was however contrary to ndings where respondents with previous CS were reluctant to have another CS because of fear of death and mockery [20] which contributed to women preferring vaginal delivery.…”
Section: Discussionsupporting
confidence: 88%
“…The choice for vaginal birth is justified in studies, especially for its advantages such as: being natural, healthy, fast recovery and providing greater autonomy for self-care and care with the newborn (2,5,(12)(13)(14) , reasons according to what was learned in the statements of the pregnant women, since the discourses point out the advantages of vaginal birth, related to the rapid recovery and quality of the relationship with the baby in the postpartum period, identified as aspects that make vaginal birth better for the mother and the baby.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of the safety provided by the cesarean section contravenes anxiety and fear of vaginal birth, justifying the desire of pregnant women for this type of birth, with the support of family members, especially of their mothers and companions who often end up guaranteeing the procedure payment (4) . A research carried out in a private medical center in northern Taiwan has shown that the medical professional can play a decisive role in choosing the cesarean section, either by presenting it as an option from the beginning of gestation, and by responding to the passive acceptance of the pregnant woman, or for supposedly leading to shared decision-making throughout gestation (5) . In Brazil, a qualitative study carried out with women who experienced both vaginal birth and cesarean section showed ambivalence of feelings: in vaginal labor, difficulty in labor as opposed to ease in recovery, being the inverse for cesarean section.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical approval was obtained from the Faculty of Medicine, Udayana University/Sanglah Hospital (493/UN.14.2/KEP/2017), and Yamaguchi Prefectural University (No. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].Before data collection, the purpose and aim of the research were explained to the participants, and they were informed about their rights. Written and verbal information wasgiven to participants, and written consentwas obtainedbefore the interview.Participants were also assured that all their responses would be kept con dential; all collected information includingaudio recordings and transcripts were securely stored and accessible only to the researchteam.This study is a part of an ongoing project (2016-2021), which was implemented in cooperationwith Udayana University and Yamaguchi Prefectural University.…”
Section: Ethical Considerationsmentioning
confidence: 99%